Effect of polymorphisms in the PPARGC1A gene on body fat in Asian Indians - Vimaleswaran, K S; Radha, V; Anjana, M; Deepa, R; Ghosh, S; Majumder, P P; Rao, M R S; Mohan, V (International Journal of Obesity, 2006)
Objective: To evaluate whether polymorphisms in the peroxisome proliferator-activated receptor-gamma coactivator-1 alpha ( PPARGC1A ) gene were related to body fat in Asian Indians. Methods: Three polymorphisms of PPARGC1A gene, the Thr394Thr, Gly482Ser and +A2962G, were genotyped on 82 type 2 diabetic and 82 normal glucose tolerant (NGT) subjects randomly chosen from the Chennai Urban Rural Epidemiology Study using PCR-RFLP, and the nature of the variants were confirmed using direct sequencing. Linkage disequilibrium (LD) was estimated from the estimates of haplotypic frequencies using an expectation–maximization algorithm. Visceral, subcutaneous and total abdominal fat were measured using computed tomography, whereas dual X-ray absorptiometry was used to measure central abdominal and total body fat. Results: None of the three polymorphisms studied were in LD. The genotype (0.59 vs 0.32, P =0.001) and allele (0.30 vs 0.17, P =0.007) frequencies of Thr394Thr polymorphism were significantly higher in type 2 diabetic subjects compared to those in NGT subjects. The odds ratio for diabetes (adjusted for age, sex and body mass index) for the susceptible genotype, XA (GA+AA) of Thr394Thr polymorphism, was 2.53 (95% confidence intervals: 1.30–5.04, P =0.009). Visceral and subcutaneous fat were significantly higher in NGT subjects with XA genotype of the Thr394Thr polymorphism compared to those with GG genotype (visceral fat: XA 148.2±46.9 vs GG 106.5±51.9 cm 2 , P =0.001; subcutaneous fat: XA 271.8±167.1 vs GG 181.5±78.5 cm 2 , P =0.001). Abdominal (XA 4521.9±1749.6 vs GG 3445.2±1443.4 g, P =0.004), central abdominal (XA 1689.0±524.0 vs GG 1228.5±438.7 g, P <0.0001) and non-abdominal fat (XA 18763.8±8789.4 vs GG 13160.4±4255.3 g, P <0.0001) were also significantly higher in the NGT subjects with XA genotype compared to those with GG genotype. The Gly482Ser and +A2962G polymorphisms were not associated with any of the body fat measures. Conclusion: Among Asian Indians, the Thr394Thr (G → A) polymorphism is associated with increased total, visceral and subcutaneous body fat.